Prevalence and determinants of complementary feeding indicators in the first year of life in the Southwest of Bahia State - Clessiane de Brito Barbosa; Elma Izze da Silva Magalhães; Daniela da Silva Rocha (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to estimate the prevalence of complementary feeding indicators and investigate its determinants. Methods: cross-sectional study with 12-month-old children from Vitória da Conquista, Bahia. The indicators minimum diet diversity, minimum meal frequency and minimally acceptable diet were constructed and adapted to the current recommendations of the food guide for Brazilian children under two years of age. Poisson regression analysis was used, with hierarchical entry of variables in the multivariate model. Results: the prevalence of minimum diet diversity was 38.8%, minimum meal frequency 47.9% and minimally acceptable diet 18.5%. Family income greater than one minimum wage was associated with minimal diet diversity (PR= 1.49; CI95%= 1.39-2.26); receiving guidance on complementary feeding was associated with a minimum meal frequency (PR= 1.37; CI95%= 1.05-1.78); and children who received exclusive breastfeeding for up to 6 months had significantly higher prevalences of all indicators compared to those who did not. Conclusions: low prevalence of complementary feeding indicators was observed. The variables family income, receiving guidance on complementary feeding and offering exclusive breastfeeding for six months were associated with the highest prevalence of the studied indicators.